Psychometric Properties and Development of a Scale Designed to Evaluate the Potential of Predatory Violent Behavior - Penagos-Corzo, Julio C.; Antonio, Alejandra A.; Dorantes-Argandar, Gabriel; Alcázar-Olán, Raúl J. (Frontiers in Psychology, 2019)
The objective of this study was to develop and determine the psychometric properties of an instrument designed to detect traits and behavior that are associated with predatory violent behavior, which is defined as a determined, planned, controlled, and proactive aggression. The sample was comprised of 546 students, mostly in their last year of high school or in their first year of college. The initial instrument had 78 items, ultimately resulting in 15 with good internal consistency (α = .825). Factor analysis showed four factors: anger-in, appeal for weapons, suicidal ideation, and the tendency to take justice into one’s own hands. Said factors showed significant correlations of convergent validity. Data shown here allows inferring that the instrument is a novel and concise tool that evaluates and detects the potential of predatory violent behavior.